ANALISA KINERJA KEUANGAN PERUSAHAAN REAL ESTATE DAN PROPERTY SEBELUM DAN SELAMA DIBERLAKUKANNYA PP NO.34 TAHUN 2016 - Mar’atus Solikhah; Jeni Susyanti; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTFinancial Performance Analysis Of Real Estate And PropertyCompanies Before And During The Implementation Of Pp No.34 Of 2016 The purpose of this study is to know and analyze whether there are differences in the financial performance of real estate companies and property before and during the enactment of PP No.34 of 2016. Comparative method is used in this study. The sample selection used purposive sampling method, so that the selected sample amounted to 40 companies. The method in collecting research data is documentation. And Paired Samples T Test technique for hypothesis testing. Based on the results of research that has been done on the real estate and property company proves that after hypothesis testing by using Paired Samples Analysis T Test, the results of differences in the variable Net Profit Samples (NPM) and Assets Turnover (AT) while the variable Current Ratio (CR), QuickRatio (QR), Debt To Equity Ratio (DER), Return On Assets (ROA) and Return OnEquity (ROE) did not occur significantly. These results have proven that after the new policy is still in transition during the enactment of PP No.34 of 2016 and still in the adjustment. Therefore, it has not been totally unevenly improving its financial performance against real estate and property companies.Keywords: Financial Performance, Corporate Income Tax, PP No.34 of 2016,real estate and property, Paired Samples T